Evaluasi Tingkat Usability Situs Belanja Online X Menggunakan Tobii-Eye Tracker dan Face Reader - -, Yanto; Salim, Regina Fortunata (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
This study aimed to evaluate the usability of a popular online shopping site. For usability testing, a number of 10 university students were recruited as participants. They were asked to perform two simulation tasks related to online shopping behaviour. Their responses were measured using Tobii Eye-Tracker and Noldus FaceReader. The results showed that the shopping online site under study could be classified as good usability with a high level of effectiveness and efficienty in using the site. The Tobii Eye-Tracker results showed that eye movement as the user's focus was on the product type, specifications, and price. Meanwhile, the FaceReader showed that most participants have neutral facial expression while runningon the site. This study also suggested that improving the performance of shopping sites can be done by focusing more on product types, specifications and prices.